(In press) Inclusive Virtual-Learning Environments for Students with Disabilities in Uganda’s Universities after COVID-19 - Musenyente, Elijah; Nyadoi, Jacinta (Indonesian Journal of Disability Studies, 2026)
The study investigated students with disabilities’ inclusion in virtual learning Environments (VLEs) in Uganda’s universities post-covid-19, focusing on identifying key elements that enhance accessibility and inclusivity to curricula; adaptable digital course materials and instructional methods for equal participation; assistive technologies and customized accommodations. The descriptive cross-sectional mixed research study gathered information using structured questionnaires (quantitative) and in-depth semi-structured interviews (qualitative) from students with disabilities studying various courses in eight universities of Uganda. The findings revealed that the adoption of inclusive online teaching methods remains surprisingly low across all the eight universities. This observation for example, is represented by 67.6% of learners with visual impairment could not read text during online lessons while 70.6% were unable to download notes in various forms, such as documents, PDFs, and audios. Further, despite the motivation of students with disabilities to succeed, they faced inadequate user-friendly accessibility features in digital educational resources, including inappropriate course materials, and lack of assistive technologies, with 92.8% of students with physical impairment lacking keyboard and mouse modifications, 69.2% of learners with hearing difficulties unable to communicate using smartphones during online lectures, and 79.4% of learners with visual impairment unable to transcribe Braille on-line using a computer. The study concluded that, promoting the inclusion of students with disabilities in VLEs necessitates recognition of limitations of hearing, intellectual, visual and physical impairment and recommends designing accessible virtual learning systems appropriate to their specific or unique individual learning needs. The study has implications of being invaluable for the Ministry of education, academic staff, administrators, ICT software instructional designers and support services to provide inclusive and user-friendly online resources as well as advocacy efforts towards overcoming obstacles encountered by students with disabilities in accessing VLEs.